Risk factors for mortality in children with Wilms tumor - Yuni Purwanti; Sutaryo Sutaryo; Sri Mulatsih; Pungky Ardani Kusuma (Indonesian Pediatric Society, 2016)
Background Wilms tumor is the most common renal malignancy in children (95%) and one of the leading causes of death in children, with high mortality rates in developing countries. Identifying risk factors for mortality is important in order to provide early intervention to improve cure rates.Objective To identify risk factors for mortality in children with Wilms tumor.Methods We performed a case-control study of children (0-18 years of age) with Wilms tumor admitted to Dr. Sardjito Hospital between 2005 and 2012. The case group consisted of children who died of Wilms tumor, whereas the control group were children who survived. Data were collected from medical records. Statistical analyses using Chi-square and logistic regression tests were done to determine odds ratios and 95% CI of the potential risk factors for mortality from Wilms tumor.Results Thirty-five children with Wilms tumor were admitted to Dr. Sardjito Hospital during the study period. Nine (26%) children died and 26 survived. Stage ≥III was a significant risk factor for mortality in chidren with Wilms tumor (OR 62.8; 95%CI 5.6 to 70.5). Age ≥2 years (OR 1.4; 95%CI 0.1 to 14.3) and male sex (OR 1.2; 95%CI 0.1 to 10.8) were not significant risk factors for mortality.Conclusion Stage ≥III is a risk factor for mortality in children with Wilms tumor.